(untitled) - Ryūji, Hattori (Tokyo, Japan, 2019)
This title examines the period from the International Military Tribunal for the Far East (the Tokyo Trial) to the normalization of relations between Japan and South Korea and between Japan and China. Chapter 1 explores issues that arose regarding Japanese history textbooks, the release of a statement by Chief Cabinet Secretary Miyazawa Kiichi, Chun Doo-hwan’s visit to Japan, and “mutual trust” with Chinese Communist Party General Secretary Hu Yaobang and Prime Minister Nakasone Yasuhiro. Chapter 2 investigates the view of the Chinese side and behind-the-scenes negotiations regarding visits by Japanese prime ministers to Yasukuni Shrine, focusing on Prime Minister Nakasone’s official visit in particular.
Keywords: Diplomatic relations,Nhật Bản,Japan,Quan hệ ngoại giao; Hợp tác quốc tế,Foreign relations,Đối ngoại